PEMBINAAN AKHLAK PADA MADRASAH ALIYAH PONDOK PESANTREN ALKHAERAAT PUSAT PALU - Gunawan B. Dulumina (Hunafa: Jurnal Studia Islamika, 2009)
This paper deals with the concept of Islamic education which has been implemented in moral education at the Islamic high school of Alkhaeraat Palu. It analyzes its concept, methods, as well as obstacles which have been confronted in this process of teaching Islamic morality. This study employs qualitative approach using case study as a method of inquiry. The result of study shows that moral education, which has been performed in this school, is based on moderate Islam, since a great deal of practical methods are employed in this process.Kata Kunci:    pembinaan akhlak, pendidikan Islam, keteladanan, pembiasaan, Madrasah Aliyah Akhaeraat